Effect of Adding RON97 Into Waste Cooking Oil as an Alternative Fuel for Diesel Engine - Saad, Idris; Hayah Ab Rashid, Wardatul; Hidayah Saidon, Nur (International Journal of Engineering and Technology, 2018)
Petroleum-based fuel reserves are drastically depleting due to a high demand on sustaining a better lifestyle. This paper presents the utilization of waste cooking oil (WCO) as an alternative fuel for diesel engine. Although WCO and conventional diesel fuel have similar physiochemical properties, the properties of WCO is considered inferior than conventional diesel fuel. It is due to higher viscosity and density of WCO while its calorific value is lower than conventional diesel fuel. In this research, unmodified WCO was blended with petrol fuel grade RON97.Â Five blended fuels samples were prepared from five to 25 percent volume base with five percent step increment. The density and calorific value of all fuel blend samples together with unmodified WCO were measured and compared to the conventional diesel and RON97 fuels. Each of the blended fuel and conventional diesel were used to run a single cylinder diesel engine. The performance characteristic of the engine was recorded at different engine speeds ranging between 1500 and 3000 rpm. Results showed that the properties of blended fuel were inferior compared to the conventional diesel fuel; however, by adding 15 percent of RON97 into the unmodified WCO, the results were comparable to the conventional diesel fuel.Â Â